2014
DOI: 10.1253/circj.cj-14-0466
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Aortic Valve Replacement With Mechanical Prosthesis or Carpentier-Edwards Perimount Bioprosthesis in Japanese Patients According to Age

Abstract: College of Cardiology guidelines revised in 2014 recommend BP for the patients aged >70 years, mechanical prosthesis (MP) for the patients aged <60 years, and either a BP or MP for the patients aged 60-70 years. 7 Due to the lack, however, of longterm results for the use of BP in AVR 8 and the small number of comparative studies 9 of different age groups in Japan, it remains debatable as to which type of prosthesis, BP or MP, is better for AVR in Japanese patients in their 60 s.The purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…The results for 5-, 10-, and 15-year freedom from SVD according to age group are consistent with the findings of other studies on CE-P valves [4,15,16,20]. The study by Marchand et al [4] revealed that for patients who had undergone either isolated MVR or combined MVR and AVR, the freedom from SVD at 5, 10, and 14 years was 99.3 ± 0.7, 83.8 ± 3.3, and 59.2 ± 6.6%, respectively, for those ≤60 years of age, 100, 94.6 ± 2.2, and 76.0 ± 6.3% for those 61-70 years of age, and 100% at both 5 and 10 years for those >70 years of age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results for 5-, 10-, and 15-year freedom from SVD according to age group are consistent with the findings of other studies on CE-P valves [4,15,16,20]. The study by Marchand et al [4] revealed that for patients who had undergone either isolated MVR or combined MVR and AVR, the freedom from SVD at 5, 10, and 14 years was 99.3 ± 0.7, 83.8 ± 3.3, and 59.2 ± 6.6%, respectively, for those ≤60 years of age, 100, 94.6 ± 2.2, and 76.0 ± 6.3% for those 61-70 years of age, and 100% at both 5 and 10 years for those >70 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…The study by Marchand et al [4] revealed that for patients who had undergone either isolated MVR or combined MVR and AVR, the freedom from SVD at 5, 10, and 14 years was 99.3 ± 0.7, 83.8 ± 3.3, and 59.2 ± 6.6%, respectively, for those ≤60 years of age, 100, 94.6 ± 2.2, and 76.0 ± 6.3% for those 61-70 years of age, and 100% at both 5 and 10 years for those >70 years of age. In a study of 313 Japanese patients who had CE-P bioprostheses for AVR, the rate of freedom from SVD at 20 years was 54.2 ± 18% for those who were 60-69 years old and 29.5 ± 15% for those who were <60 years old [20]. These findings, similar to ours, suggested (1) that freedom from SVD differed between age groups, as seen in the patients ≥70 years, who infrequently developed SVD at 10 years or more following valve replacement, and (2) that SVD was more likely to occur in patients of the age group <60 years.…”
Section: Discussionmentioning
confidence: 99%
“…5 In particular, this study is unique because we compared these 2 types of valves using propensity score analysis by stratifying a large cohort according to the age cut-offs 60 and 70 years, as noted in the most recent ACC/AHA treatment guidelines. 1 We, as clinicians in daily practice, must insure that patients and their families are fully informed about the risks and benefits of both types of prosthetic valves, and we must allow them to decide based on this information.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been numerous retrospective cohort studies comparing the outcomes of tissue vs. mechanical valves, 30 there have been only a few prospective randomized control clinical trials comparing tissue and mechanical prostheses. In the Veterans Administration Cooperative Study on Valvular Heart Disease, Hammermeister et al concluded that patients who underwent AVR with mechanical valves had better survival at 15 years than those who received tissue valves.…”
Section: Discussionmentioning
confidence: 99%